IMPLEMENTASI PERDA NO. 8 TAHUN 2020 DALAM OPTIMALISASI PROMOSI DIGITAL PARIWISATA BERKELANJUTAN DI KABUPATEN GUNUNGKIDUL - Tanti Apriyani; Vibriza Juliswara (Journal of Indonesian Rural and Regional Government, 2026)
Gunungkidul Regency, as one of the leading tourist destinations in the Special Region of Yogyakarta, has enacted Regional Regulation Number 8 of 2020 concerning Tourism Implementation, which emphasizes the use of information technology and the principles of sustainable tourism. This study aims to understand the implementation of Gunungkidul Regency's tourism promotion policy in the context of optimizing digital media. The method used in this study is qualitative with a descriptive approach. The selection of research informants used a purposive sampling method. Data collection techniques were carried out through interviews, observation, and documentation. The results show that the implementation of digital promotion policies in Gunungkidul Regency has made a positive contribution to increasing the exposure of tourist destinations. The promotional strategies implemented include the use of social media, collaboration with influencers, and the implementation of pentahelic in tourist villages, which includes collaboration between the government, academics, local communities, business actors, and the media. Several obstacles include inequality in access to technology, especially weak internet networks in coastal and mountainous areas. In addition, limited human resources who master digital technology, the lack of supporting facilities such as MPOS (Mobile Point of Sales), and the absence of SOPs and specific regulations related to digital promotion are challenges in themselves. This research offers a novel analysis of regional policy implementation that integrates digital promotion with sustainable tourism principles at the local government level.